Reliability analysis for systems with self-healing mechanism under two different types of cumulative shocks. Issue 4 (4th July 2022) - Kang, Fengming; Cui, Lirong
ABSTRACT: System with self-healing mechanism has been successfully applied in many practical engineering fields. When we discuss the reliability performance of system subject to shocks, cumulative shocks have the greatest impact on most systems fields such as high-speed railway systems or civil structural components. In the present paper, we deal with two different types of cumulative shock models in discrete time with self-healing effect. We study a system with self-healing mechanism from a reliability point of view under these two shock models. The self-healing system will fail when the cumulative damage effect exceeds the given threshold. In the first model, there are shock events at instant of time i ( i = 1, 2, … ), while in the second model at some time point there was no shock occurring event. Along with the work in this article, the system reliability formulas and the means and variances of their lifetimes are given under two different types shock models proposed, then simulation methods are adopted to analyze the reliability of the system for the second cumulative model. Finally, numerical examples and future researches are discussed.